Crystal structure and magnetic properties of SrCaMnGaO5+delta - Battle, P; Bell, A; Blundell, S; Coldea, A; Gallon, D; Pratt, F; Rosseinsky, M; Steer, C (2002)
The room-temperature crystal structure of the brownmillerite SrCaMnGaO5+δ (δ = 0.035) has been refined from neutron powder diffraction data; space group Ima2, a = 15.7817(6), b = 5.4925(2), c = 5.3196(2) Å. Mn and Ga occupy 99.0(2)% of the 6- and 4-coordinate sites, respectively. A combination of magnetometry, neutron diffraction and μSR spectroscopy has shown that the compound orders magnetically at 180 K, and that the low-temperature phase has a G-type antiferromagnetic structure, with an ordered magnetic moment of 3.30(2) μB per Mn at 2 K. Displaced hysteresis loops provide evidence that the atomic moment has an additional, glassy component. Magnetometry shows that significant short-range magnetic interactions persist above 180 K, and μSR that the spin fluctuations are thermally activated in this temperature region. The compound is an electrical insulator which at 159 K shows an unusually large magnetoresistance of 85% in 6T, increasing to 90% in 13 T. © 2002 Elsevier Science (USA).